Faktor-Faktor Yang Mempengaruhi Minat Pengguna Sistem Informasi Akuntansi Berbasis Dompet Digital (Studi Empiris Pada Mahasiswa Akuntansi Universitas Sains Al-Qur’an) - wulandari, wulandari; Mutmainah, Kurniawati; Maulidi, Rizky (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2025)
The development of digital technology has advanced payment systems in Indonesia, including the implementation of Accounting Information Systems based on digital wallets (e-wallets), which simplify payments. This study analyzes factors influencing interest in using such systems, employing a quantitative method with 517 Accounting students at Universitas Sains Al-Qur’an, Central Java, as the population. A sample of 84 respondents was selected using the Taro Yamane formula, and data were analyzed with multiple linear regression using SPSS version 25. The findings reveal that among six tested variabels, only perceived usefulness (significance 0.005) significantly influences interest in using digital wallets. Other variabels, such as perceived ease of use, security, risk, trust, and financial literacy, have no significant effect. In conclusion, perceived usefulness and security are key factors driving interest in using Accounting Information Systems based on digital wallets.